Spatial Distribution, Isolation, and Characterization of Morphological Variants of the Fusarium Wilt Pathogen in Brinjal Across Andhra Pradesh and Tamil Nadu, India - , Mule Harindra Reddy, S. Sundaramoorthy (Archives of Current Research International, 2025)
Fusarium wilt, caused by various Fusarium species, is a devastating disease of brinjal (Solanum melongena) leading to substantial yield losses in major production regions. This study aimed to assess the prevalence of Fusarium wilt in Tamil Nadu and Andhra Pradesh during 2024. A comprehensive survey across brinjal-growing regions, including Chittoor, Kurnool, Guntur, Salem, Dindigul, Krishnagiri, and Cuddalore, revealed varying disease incidence. Hosur (Tamil Nadu) exhibited the highest percent disease incidence (PDI) at 56.45%, followed by Madanapalli (Andhra Pradesh) at 54.67%. Pathogen isolation and identification using the tissue segment method confirmed Fusarium sp. as the primary causal agent. Morphological characterization revealed significant variations among isolates in colony shape, conidial diameters, and growth patterns, indicating a heterogeneous Fusarium population across the investigated locations. To lessen the effect of Fusarium wilt on brinjal output, these results highlight the vital necessity for ongoing monitoring, precise pathogen identification, and the creation of integrated management techniques such resistant variety breeding.